Effect of selenium and melatonin on some parameters Related to metabolic syndrome induced by Acryl amide in male rats (Part I): Rawnah Isam Sabeeh and Khalisa Khadim Khudair - Khudair, Khalisa Khadim (The Iraqi Journal of Veterinary Medicine, 2017)
This study was designed to investigate the ameliorative role of sodium selenite and melatonin on acryl amide induced metabolic syndrome in adult male rats. Twenty (20) adult male rats were randomly and equally divided into 4 groups (G1, G2, G3 and G4) and were treated orally for seven weeks G1, (control group) was given distilled water, G2 were given orally 1mg/kg /B.W of Acryl amide, G3 group received 1mg/kg /B.W of Acryl amide followed by 0.5 mg/Kg/ B.W. of sodium selenite orally. G4 group received 1 mg/kg /B.W of acryl amide (orally) followed by 8 mg/Kg/ B.W. melatonin (IP/ injection). Fasting blood samples were collected by cardiac puncture at (0, 7 weeks) of the experiment for measuring serum total cholesterol, triacylglycerol, high density lipoprotein-cholesterol and serum uric acid, in addition to measuring waist circumference .The results showed an occurrence of central obesity, hyper uricemia, dyslipidemia (hyper cholesterolemia, triacyleglycerolemia and lowered high density lipoprotein-cholesterol concentration) in acryl amide treated animals. The results also indicated the alleviation of the changes in the above- mentioned parameters related to metabolic syndrome by sodium selenite and melatonin through lowering central obesity, total cholesterol, triacylglycerol, elevation of serum high density lipoprotein-cholesterol and lowering in serum uric acid.